Genetic Expression of ALDH2 and ADH1B in Alcoholic Dependent Individuals in Iraqi Population - Kadhim, Ali Qahtan; Al-Khalidi, Rasha Abd Ali (Iraqi Journal of Science, 2026)
Alcohol addiction is a public health concern that affects communities all over the world, especially those with distinct genetic traits, such as the Iraqi community. This study investigates the genetic factors that contribute to alcohol dependence, focusing on the expression levels of Alcohol Dehydrogenase 1B (ADH1B) and Aldehyde Dehydrogenase 2 (ALDH2) genes in individuals from diverse regions of Iraq. A total of 250 blood samples were collected from males, ranging in age from 18 to 55, including 200 alcohol-dependent individuals and 50 samples as controls in the Iraqi population. The data showed a considerable increase in the expression level of the ADH1B (P-value < 0.0001; t= 6.447) among alcohol-dependent individuals compared to the control group. At the same time, the expression level of the ALDH2 gene is significantly downregulated (P-value < 0.0001; t = 6.447) in alcohol-dependent individuals compared to the control. In alcohol dependence, ADH1B and ALDH2 transcripts demonstrate different patterns that enable more efficient alcohol breakdown and protection against toxic aldehyde buildup. Alcohol detoxification roles of these enzymes demonstrate an extremely positive correlation through the result of r = 0.8347 with p > 0.0001. The protective mechanism between ADH1B and ALDH2 becomes less effective when alcohol addiction continues, causing metabolic problems as well as disease development. The research confirms the essential metabolic interactions between ADH1B and ALDH2 regarding alcohol dependence while showing the requirement for additional studies about their medical applications for prevention and therapy. Finally, the work reinforces the importance of genetic screening of these markers as possible tools for diagnosing individuals at risk for alcohol use disorders and establishing personalized therapy strategies to address the metabolic disturbances associated with alcohol dependency.